Total laparoscopic hysterectomy versus total abdominal hysterectomy for obese women with endometrial cancer. Issue 2 (1st February 2005) - Obermair, A.; Manolitsas, T. P.; Leung, Y.; Hammond, I. G.; Mccartney, A. J.
Abstract : Obesity is common in endometrial cancer and surgery for these patients is challenging. We compared total laparoscopic hysterectomy (TLH) with total abdominal hysterectomy (TAH) with respect to feasibility (operating time, estimated blood loss, length of hospital stay, and conversion to laparotomy) and safety (perioperative morbidity and mortality) in a retrospective analysis of 78 morbidly obese patients with endometrial cancer. Analysis is based on the intention to treat. The intention to treat was TLH in 47 patients and it could be successfully completed in 42 patients (89.4%). The mean weight for all patients was 118.7 kg, with patients in the TLH group weighing more and having higher ASA scores. Mean operating time and estimated blood loss were similar in both groups. Mean postoperative hospital stay was 4.4 (±3.9) days in the TLH group and 7.9 (±3.0) days in the TAH group (P < 0.0001). Wound infections occurred in 15 of 31 patients (48.4%) in the TAH group and in 1 of 47 patients (2.1%) in the TLH group. All other morbidity, as well as patterns of recurrence and survival were similar in both groups. These data justify a prospective randomized trial comparing TLH with TAH for the treatment of endometrial cancer